Treatment with essential oil of Achyrocline satureioides in rats infected with Trypanosoma evansi: Relationship between protective effect and tissue damage - Baldissera M.D. (2014)
© 2014 Elsevier GmbH.The aim of this study was to evaluate the effects of treatment with free and nanoencapsulated essential oil of Achyrocline satureioides on trypanosomosis and its oxidative/antioxidants variables in liver and kidney of rats infected experimentally with Trypanosoma evansi. For that, 48 rats were divided into six groups (A-F), eight animals each group. Groups A, C and D were composed of uninfected animals, while animals in groups B, E and F were inoculated intraperitoneally with T. evansi. Groups A and B were used as controls, negative and positive, respectively. Groups C and E receive oil (orally), as well as the animals in groups D and F were treated with nanoencapsulated essential oil. The treatment was not able to eliminate the parasites, but it remained the levels of parasitemia low. The carbonyl levels in liver and kidney did not differ between groups. Infected animals (group B) showed an increase in the TBARS levels and a decrease in the CAT activity and NPSH levels in liver and kidney, compared with the same parameters in the control (group A). Treatment with A. satureioides (groups C and D) did not influence the TBARS levels and CAT activity in the liver, but it increased the CAT activity in kidneys of the animals of group C. NPSH levels decreased in liver in the groups treated with nanoencapsulated essential oil (groups D and F). An interesting result observed was that the animals infected and then treated with essential oil of A. satureioides (groups E and F) did not differ from animals of group A for TBARS, CAT and NPSH, unlike what happened with the animals of group B. Therefore, the treatment with essential oil did not eliminate the parasites from the bloodstream, but it reduced the number of trypanosomes, mainly by its nanoencapsulated form. The same occurred with the lipid peroxidation in the liver. However, the treatments reduced the oxidative damage, and it led to the activation of the antioxidant enzymes. We believe that the association of this natural product with a trypanocidal drug may enhance its curative effect.